Potential Carbon Stock and CO2 Absorption in Star Apple (Chrysophyllum cainito) and Javanese Sapodilla (Manilkara kauki) in the Unesa Campus Forest - Rifah, Fitriah Anggun Juwita Ma; Rachmadiarti, Fida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The Unesa Campus Forest is one of the green open spaces that has the to play a significant role in mitigating climate change through carbon storage and sequestration. However, information on the carbon storage capacity and CO₂ absorption of local tree species in this area is still limited. This study aims to analyze the carbon stock and CO2 absorption in C. cainito and M. kauki in the Unesa campus forest and their relationship with morphological and physiological characteristics as well as physical and chemical parameters of the environment carbon stocks and CO2 absorption in C. cainito and M. kauki in the Unesa campus forest and to examine their relationships with morphological and physiological characteristics, as well as with physical and chemical environmental parameters. The study employed a total census and purposive sampling method, with analysis of the relationship between variables using Pearson's correlation test. The results showed that M. kauki has higher carbon stock and CO₂ absorption capacity than C. cainito. Carbon stock was positively correlated with height, circumference, diameter, and leaf area of C. cainito and M. kauki. Meanwhile, chlorophyll content for did not significantly affect carbon stock. The physicochemical parameters of the environment in this study supported the growth of both plant species.